2013
DOI: 10.1002/adsc.201200881
|View full text |Cite
|
Sign up to set email alerts
|

Green and Scalable Aldehyde‐Catalyzed Transition Metal‐Free Dehydrative N‐Alkylation of Amides and Amines with Alcohols

Abstract: In contrast to the borrowing hydrogentype N-alkylation reactions, in which alcohols were activated by transition metal-catalyzed anaerobic dehydrogenation, the addition of external aldehydes was accidentally found to be a simple and effective protocol for alcohol activation. This interesting finding subsequently led to an efficient and green, practical and scalable aldehyde-catalyzed transition metal-free dehydrative N-alkylation method for a variety of amides, amines, and alcohols. Mechanistic studies reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 69 publications
1
50
0
Order By: Relevance
“…of benzyl alcohols under similar reaction conditions (Scheme ). The formation of dialkylated products was justified by the electron‐rich nature of five‐membered thiazole in comparison to other six‐membered heterocycles, and explained by the mechanism depicted in Scheme …”
Section: Tm‐free Dehydrative C−n Forming Reactions With Alcoholsmentioning
confidence: 99%
See 2 more Smart Citations
“…of benzyl alcohols under similar reaction conditions (Scheme ). The formation of dialkylated products was justified by the electron‐rich nature of five‐membered thiazole in comparison to other six‐membered heterocycles, and explained by the mechanism depicted in Scheme …”
Section: Tm‐free Dehydrative C−n Forming Reactions With Alcoholsmentioning
confidence: 99%
“… Proposed MPV‐transition states involved in the TM‐free transfer hydrogenation reactions from alcohols to imines …”
Section: Tm‐free Dehydrative C−n Forming Reactions With Alcoholsmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening of the reaction conditions revealed that both the ketone and base are essential (see Table S1, entries 2-4). This ketone-catalyzed amination appears to be reminiscent of the aldehyde-catalyzed achiral alkylation reactions reported by Xu, [22] Kang,[22b] and co-workers,i nw hich ac atalytic amount of an aldehyde initiates the reaction with the catalysis sustained by aldehyde subsequently generated. This ketone-catalyzed amination appears to be reminiscent of the aldehyde-catalyzed achiral alkylation reactions reported by Xu, [22] Kang,[22b] and co-workers,i nw hich ac atalytic amount of an aldehyde initiates the reaction with the catalysis sustained by aldehyde subsequently generated.…”
Section: Identification Of Ametal-free Asymmetric Amination Protocolmentioning
confidence: 99%
“…[22] Thus,t aking the amination of 2a with 1 as an example,the initially-introduced catalytic ketone would react reversibly with 1 to form the imine (R)-17,t he reduction of which by the sodium salt of racemic 2a would then afford the diaseteromerically pure 3a, while releasing one new ketone molecule and the base used in forming the alkoxide from 2a( Figure 6). [22] Thus,t aking the amination of 2a with 1 as an example,the initially-introduced catalytic ketone would react reversibly with 1 to form the imine (R)-17,t he reduction of which by the sodium salt of racemic 2a would then afford the diaseteromerically pure 3a, while releasing one new ketone molecule and the base used in forming the alkoxide from 2a( Figure 6).…”
Section: Forschungsartikelmentioning
confidence: 99%